Magnetic Intramedullary Lengthening Nails and MRI Compatibility. Issue 10 (November 2018) - Gomez, Charles; Nelson, Scott; Speirs, Joshua; Barnes, Samuel
Abstract : Background: Magnetic intramedullary nails (IMNs) are fully implantable lengthening devices that became available in the United States in 2011 for the correction of limb length discrepancies. This device represents a major advancement in the field of limb lengthening surgery as it is typically tolerated better than external fixation. Unlike traditional IMNs, surgeons recommend routine removal following limb lengthening. One such reason involves patient safety as it pertains to magnetic resonance imaging (MRI). Theoretical concerns with MRI exposure include implant migration, implant heating, and involuntary elongation of the lengthening mechanism. Our study seeks to investigate the effects of MRI on intramedullary magnetic lengthening nails. Methods: Twenty-five intramedullary magnetic nails were studied. One nail was placed within the magnetic field to measure maximum magnetic force. Nails were then scanned using standard knee MRI protocols, 12 in 3 T and 12 in 1.5 T MRI scanners. The following parameters were measured: (1) distraction of the implants after MRI exposure, (2) temperature before and after MRI, and (3) internal distraction force before and after MRI. Results: Maximum magnetic force was found to be 2 lbs. There was no involuntary distraction of the implants after MRI. Temperature increase of 3.3°C was found in the femoral nails and 3.6°C in the tibial nails that were exposed to 3 T MRI. This increase did not reach or exceed physiological temperature of 37°C. Distraction force was reduced by 61.7% in the femoral nails and 89.6% in the tibial nails after subjected to 3 T MRI. There was no reduction in distraction force after exposure to 1.5 T MRI. Conclusions: Recommendations for routine removal of magnetic IMNs for safety concerns should be reconsidered. Exposure to 3 T MRI should be avoided in patients who are still undergoing lengthening or with plans for future lengthening with magnetic IMNs. Clinical Relevance: To assess patient safety and implant function after magnetic IMNs have been exposed to MRI.